Ultrasonic and Acoustic Investigation of Binary Mixtures of Ethyl Benzoate and 2 Methyl 1 Propanol at Different Temperatures - LakshmanaRao G,; Suresh P,; Beebi SK,; Sailaja G, (International Journal of Scientific Research in Science and Technology, 2026)
Ultrasonic velocity (U), density (ρ) and viscosity (η) of the binary liquid mixture consisting of ethyl benzoate (X₁) and 2 methyl 1 propanol (X₂) were measured over the entire mole fraction range at temperatures 303.15, 308.15, 313.15 and 318.15 K. From the experimental data, several acoustical and thermodynamic parameters such as molar volume (V), adiabatic compressibility (β_ad), intermolecular free length (L_f), internal pressure (π), acoustic impedance (Z) and enthalpy (H) were evaluated. The variation of these parameters with composition and temperature has been used to understand the nature and strength of molecular interactions in the mixture. The results indicate the presence of specific interactions, mainly hydrogen bonding and dipole–dipole interactions, between unlike molecules.
Keywords: Ultrasonic velocity; Ethyl benzoate; 2 methyl 1 propanol; Acoustic parameters; Molecular interactions